Constitutional Interpretation: between dynamic and integrity - Clève, Clèmerson Merlin (2016)
This article talks about the constitutional interpretation from the perspective of two normative theories of jurisdiction: on one hand, Ronald Dworkin’s law as integrity; on the other, William Eskridge’s dynamic statutory interpretation.The theories are presented as indications for the debate about who has the best conditionsto make decisions on hard cases. Therefore, the article points out some changes that occurred lately on the constitutional jurisdiction, presents key aspects of the theories in focus and outlines commonalities and differences between the dynamic statutory interpretation and the theory of law as integrity.